A local numerical solution of a fluid-flow problem on an irregular domain. (June 2018) - Kosec, G.
Highlights: A local numerical approach for solving flow problems on complex domains is formulated. Behavior of spatial discretization is thoroughly elaborated. Approach is verified on lid driven cavity and backward facing step problems. Solution of lid driven cavity on a randomly generated domain is presented. Abstract: This paper deals with a numerical solution of an incompressible Navier-Stokes flow on non-uniform domains. The numerical solution procedure comprises the Meshless Local Strong Form Method for spatial discretization, explicit time stepping, local pressure-velocity coupling and an algorithm for positioning of computational nodes inspired by Smoothed Particles Hydrodynamics method. The presented numerical approach is demonstrated by solving a lid driven cavity flow and backward facing step problems, first on regular nodal distributions up to 315, 844 (562 × 562) nodes and then on domain filled with randomly generated obstacles. It is demonstrated that the presented solution procedure is accurate, stable, convergent, and it can effectively solve the fluid flow problem on complex geometries. The results are presented in terms of velocity profiles, convergence plots, and stability analyses.